A Decade of Sexist Entertainment: A Critical Discourse Analysis on Female Celebrities Encountering Sexism and Sexual Harassment in Interviews - Ruotsalainen, Rosalia (My University, 2022)
This is a qualitative study focusing on the issue of sexism and how it is disseminated as entertainment in the media. The research utilizes Lazar’s feminist critical discourse analysis, an approach that combines aspects from critical discourse analysis and feminist studies. Other analytic tools utilized in this research are politeness theory by Brown and Levinson and frame analysis by Goffman. The analysis consists of an examination of ten celebrity interviews which are gathered from YouTube. The main purpose of this study is to critically examine and reveal how sexist language and sexual harassment manifest in celebrity interviews between a male interviewer and a female interviewee and whether the perpetrator of these acts gets confronted. Examining whether sexism gets confronted is important because it provides information on whether sexism is perceived as behavior that needs/ is dared to be addressed. One purpose of this study is also to demonstrate how elements affecting the power imbalance, such as gender, can influence the course of the conversation. Another aim of this study is to analyze how the interviews are framed, that is how the interviews are described for the viewer and how these descriptions, that is the headings may alter the viewers perception of the interactions. The findings of this study suggest that the most common form of sexism in the material was subtle sexism, followed by sexual objectification. As disseminating sexism as entertainment may negatively impact several different individuals, from the recipient of the act to the witnesses, this study revealed a gap in the entertainment industry that must be addressed. Moreover, an alarming issue arising from the findings is that sexist language and even sexual harassment tends to not get confronted, which is another problem that needs to be addressed.
Keywords: sexism, sexual harassment, critical discourse analysis, feminist critical discourse analysis, politeness theory, frame analysis, celebrity interviews